Effects of Duckweed Meal Supplementation in Un-processed and Extruded Diets on Performance and Economics of Broilers - Inderpal Singh; J.S. Lamba; R.S. Grewal; Udeybir Singh; Daljeet Kaur; Meera D. Ansal (Indian Journal of Animal Nutrition, 2023)
A study was conducted for nutritional evaluation of duckweed meal (DWM) as an alternate protein source in broilers. DWM supplemented in un-processed and extruded diets and performance of broilers was observed. 256 IBL-80, day old commercial broiler chicks were randomly distributed into eight treatments with, four replicates each. The treatments were divided into two dietary groups: Un-processed dietary group and Extruded dietary group. Both groups were having 4 treatments. Each replicate was housing eight birds (8×4×8). Treatment T1 in both groups served as control treatment with 0% DWM, treatment T2, T3 and T4 were supplemented with 2, 4 and 6 % DWM. In both dietary groups significant differences for feed conversion ratio (FCR) was observed only during starter phase. In unprocessed dietary group best FCR, protein efficiency ratio (PER) and calorie efficiency ratio (CER) was observed for 2% duckweed meal supplemented group whereas in extrusion processed dietary group the best FCR, PER and CER was observed for 4% duckweed treatment. The results indicated that duckweed meal can be safely included in the broiler ration at 2 % level without treatment and at 4% level if used in extruded form.